Defending against Buffer-Overflow Vulnerabilities - Padmanabhuni, B.; Hee Beng Kuan Tan (Computer (Long Beach, Calif.), 2011)
A survey of techniques ranging from static analysis to hardware modification describes how various defensive approaches protect against buffer overflow, a vulnerability that represents a severe security threat.